Analysis of Genes Involved in Ulcerative Colitis Activity and Tumorigenesis Through Systematic Mining of Gene Co-expression Networks - Shi, Wanting; Zou, Rongjun; Yang, Minglei; Mai, Lei; Ren, Jiangnan; Wen, Jialing; Liu, Zhaoshi; Lai, Renxu (Frontiers in Physiology, 2019)
Ulcerative colitis (UC) is an idiopathic, chronic inflammatory disorder of the colon, characterized by continuous mucosal inflammation. Recently, some studies have considered it as part of an inflammatory bowel disease-based global network. Herein, with the aim of identifying the underlying potential genetic mechanisms involved in the development of UC, multiple algorithms for weighted correlation network analysis (WGCNA), principal component analysis (PCA), and linear models for microarray data algorithm (LIMMA) were used to identify the hub genes. The map of platelet activation, ligand-receptor interaction, calcium signaling pathway, and cAMP signaling pathway showed significant links with UC development, and the hub genes CCR7, CXCL10, CXCL9, IDO1, MMP9, and VCAM1, which are associated with immune dysregulation and tumorigenesis in biological function, were found by multiple powerful bioinformatics methods. Analysis of The Cancer Genome Atlas (TCGA) also showed that the low expression of CCR7, CXCL10, CXCL9, and MMP9 may be correlated with a poor prognosis of overall survival (OS) in colorectal cancer (CRC) patients (all p<0.05), while no significance detected in both of IDO1 and VCAM1. In addition, low expression of CCR7, CXCL10, CXCL9, MMP9, and IDO1 may be associated with a poor prognosis in recurrence free survival (RFS) time (all p<0.05), but no significant difference was identified in VCAM1. Moreover, the NFKB1, FLI1, and STAT1 with the highest enrichment score were detected as the master regulators of hub genes. In summary, these results indicated the central role of the hub genes of CCR7, CXCL10, CXCL9, IDO1, VCAM1, and MMP9, in response to UC progression, as well as the development of UC to CRC, thus shedding light on the molecular mechanisms involved and assisting with drug target validation.